Group trust model based on subjective logic - WANG Yong1; DAI Gui-ping2; JIANG Zheng-tao3; HOU Ya-rong1 (Tongxin xuebao)
Today’s dynamic trust model only research one to one trust relation and there are no researches about one to many,many to one,many to many trust relation.Based on subjective logic,four basic group constraint patterns and their nesting to compose a group were proposed at the point of view of trust’s subjectivity and supports group trust relation.A group dynamic trust model based on these four basic constraint patterns was proposed,and direct trust degree and recommendation trust degree formulae of basic constraint patterns and their nesting were brought up.The model has good applicability and practicability through model’s expressive power analysis and model’s validity analysis.